The MYCN-HMGA2-CDKN2A pathway in non-small cell lung carcinoma—differences in histological subtypes. Issue 1 (December 2016) - Eide, Hanne; Halvorsen, Ann; Bjaanæs, Maria; Piri, Hossein; Holm, Ruth; Solberg, Steinar; Jørgensen, Lars; Brustugun, Odd; Kiserud, Cecilie; Helland, Åslaug
Abstract Background Extensive research has increased our understanding of the molecular alterations needed for non-small cell lung cancer (NSCLC) development. Deregulation of a pathway including MYCN, HMGA2 and CDKN2A, with the participation of DICER1, is of importance in several solid tumours, and may also be of significance in the pathogenesis of NSCLC. Methods Gene expression ofMYCN, HMGA2, CDKN2A andDICER1 were investigated with RT-qPCR in surgically resected NSCLC tumour tissue from 175 patients. Expression of the let-7 microRNA family was performed in 78 adenocarcinomas and 16 matching normal lung tissue samples using microarrays. The protein levels of HMGA2 were determined by immunohistochemistry in 156 tumour samples and the protein expression was correlated with gene expression. Associations between clinical data, including time to recurrence, and expression of mRNA, protein and microRNAs were analysed. Results Compared to adenocarcinomas, squamous cell carcinomas had a median 5-fold increase in mRNA expression ofHMGA2 (p  = 0.003). A positive correlation (r  = 0.513, p  < 0.010) betweenHMGA2 mRNA expression and HMGA2 protein expression was seen. At the protein level, 90 % of the squamous cell carcinomas expressed high levels of the HMGA2 protein compared to 47 % of the adenocarcinomas (p  < 0.0001).MYCN was positively correlated withHMGA2 (p  < 0.010) andDICER1 mRNA expression (p  < 0.010), and the expression of the let-7 microRNAs seemed to be correlated with the genes studied.MYCN expression was associated with time to recurrence in multivariate survival analyses (p  = 0.020). Conclusions A significant difference inHMGA2 mRNA expression between the histological subtypes of NSCLC was seen with a higher expression in the squamous cell carcinomas. This was also found at the protein level, and we found a good correlation between the mRNA and the protein expression of HMGA2. Moreover, the expression ofMYCN, HMGA2, andDICER1 seems to be correlated to each other and the expression of thelet7 -genes impacted by their expression.MYCN gene expression seems to be of importance in time to recurrence in this patient cohort with resected NSCLC.